2021
DOI: 10.30723/ijp.v19i49.608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transition Metal Dopant on the Electrical Properties of ZnO-TiO2 Films Prepared by PLD Technique

Abstract: In this article, the influence of group nano transition metal oxides such as {(MnO2), (Fe2O3) and (CuO)} thin films on the (ZnO-TiO2) electric characteristics have been analyzed. The prepared films deposited on glass substrate laser Nd-YAG with wavelength (ℷ =1064 nm) ,energy of (800mJ) and number of shots (400). The density of the film was found to be (200 nm) at room temperature (RT) and annealing temperature (573K).Using DC Conductivity and Hall Effect, we obtained the electrical properties of the films. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Using Hall Effect measurements, thin films of the pure and Cu-doped MnO with varying concentrations of Cu (0.03, 0.05, 0.07, and 0.09 wt%) were examined. By measuring the Hall voltage (V H ) produced by the Hall field throughout the sample thickness (t), the Hall coefficient (R H ) was calculated [42,43]:…”
Section: Hall Effectmentioning
confidence: 99%
“…Using Hall Effect measurements, thin films of the pure and Cu-doped MnO with varying concentrations of Cu (0.03, 0.05, 0.07, and 0.09 wt%) were examined. By measuring the Hall voltage (V H ) produced by the Hall field throughout the sample thickness (t), the Hall coefficient (R H ) was calculated [42,43]:…”
Section: Hall Effectmentioning
confidence: 99%
“…The films' conductivity rose when doped with metal oxides, and the maximum conductivity was achieved when treated according to the type of doped metal oxide. According to Hall Effect investigations, each film has both n and p charge carriers [8]. Joginder, et al (2022) showed that titanium dioxide (TiO2) thin films have a wide range of uses, and the various structures of the produced films can result in new or improved features.…”
Section: Introductionmentioning
confidence: 99%